Thyroid function in full-term small-for-gestational-age (SGA) children during rGH-therapy - Muz, Nataliia; Bolshova, Olena (ScienceRise: Medical Science, 2017)
There was not established any influence of the treatment with the recombinant growth hormone (rGH) on the thyroid function in full-term small-for-gestational age SGA) children. The aim of the research was the study of the level of serum thyroxin of free (Т4) and thyrotropic hormone (TTH) in SGA children before and after rGH treatment; determination of possible influence of a body mass and length at birth, thyroid hormones on the further spontaneous growth. Methods. The research included 58 full-term SGA children (25 with spontaneous growth, 33 undersized), pre-pubertal. The measuring of levels of free T4 and TTG was realized before and in 6 and 12 months after rGH treatment. Results. Indices of free T4 and TTG don’t correlate with a standard deviation score (SDS) of a body mass and length at birth, body mass index and IGF-1. The average level of free T4 was decreasing during the first 6 months of rGH treatment, but remained within norm. TTG didn’t change during the treatment. The change of free T4 doesn’t correlate with the change of SDS of the growth speed during 12 months after rGH treatment. Conclusion. TG level doesn’t correlate with SDS of a body mass and body length at birth. The level of free Т4 decreases at rGH treatment, but it is not connected with TTG increase and doesn’t influence rGH treatment effectiveness. As far as such inessential changes in the thyroid function are not clinically important, frequent observation on the thyroid function at rGH treatment is not substantiated in full-term SGA children. Monitoring in such children must be realized once a year with determining TTG and free Т4 levels in blood plasma